Personal Branding Cut Fatimah Didasarkan pada Representasi Followers Media Sosial Instagram @cutfatimahhh - Livia Devi Octaviany; Yasser Fikry (UNISBA Press, 2023)
Abstract. With the advent of Instagram, new influencers have been born seeking public recognition. To become an influencer, of course, requires good personal branding in the eyes of the general public. Representation is an arrangement (shape or arrangement) that can represent, state or symbolize something by conveying or expressing something. The purpose of this study was to determine the personal branding based on the representation of Instagram Social Media Followers @cutfatimahhh. This research uses a qualitative approach with descriptive methods. This study uses an interpretive paradigm. The results of this study are that Cut Fatimah maintains her personal branding by creating content that complies with norms and laws, creating quality content, and always reviewing comments made by netizens. According to informants, Cut Fatimah deserves to be called an influencer/celebgram because she really inspires her followers through content uploaded on her Instagram social media, namely mix and match simple hijab fashion. Cut Fatimah is certainly different from other celebrity programs both in terms of the quality of the content, the contents are in accordance with their characteristics. Cut Fatimah's personal branding through her Instagram social media has fulfilled 8 main concepts of personal branding, namely: Specialization (The Law of Specialization), Leadership (The Law of Leadership), Personality (The Law of Personality), Difference (The Law of Distinctiveness), Visible (The Law of Visibility), Unity (The Law of Unity), Firmness (The Law of Persistence), Good Name (The Law of Goodwill). Abstrak. Dengan munculnya Instagram, influencer baru telah lahir untuk mencari pengakuan publik. Untuk menjadi seorang influencer, tentu membutuhkan personal branding yang baik di mata masyarakat umum. Representasi adalah susunan (bentuk atau susunan) yang dapat mewakili, menyatakan atau menyimbolkan sesuatu dengan cara menyampaikan atau mengungkapkan sesuatu. Tujuan penelitian ini dilakukan adalah untuk mengetahui personal branding didasarkan pada representasi Followers Media Sosial Instagram @cutfatimahhh. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Penelitian ini menggunakan paradigma interpretif. Hasil dari penelitian ini adalah Cut Fatimah mempertahankan personal brandingnya dengan cara membuat konten yang sesuai dengan norma dan hukum, membuat konten yang berkualitas, selalu mereview komentar-komentar yang dibuat oleh netizen. Menurut para informan, Cut Fatimah layak dikatakan sebagai influencer/selebgram karena sangat menginspirasi para followersnya melalui konten yang diunggah di media sosial Instagramnya yaitu mix and match fashion hijab simple. Cut Fatimah tentu berbeda dengan selebgram lainnya baik dari segi kualitas konten, isi konten sesuai dengan ciri khasnya. Personal branding Cut Fatimah melalui media sosial Instagramnya sudah memenuhi 8 konsep utama personal branding, yaitu Spesialisasi (The Law of Specialization), Kepemimpinan (The Law of Leadership), Kepribadian (The Law of Personality), Perbedaan (The Law of Distinctiveness), Terlihat (The Law of Visibility), Kesatuan (The Law of Unity), Keteguhan (The Law of Persistence), Nama Baik (The Law of Goodwill).